Molecular detection of Anaplasma infections in ixodid ticks from the Qinghai-Tibet Plateau - Rong Han; Ji-Fei Yang; Muhammad Uzair Mukhtar; Ze Chen; Qing-Li Niu; Yuan-Qing Lin; Guang-Yuan Liu; Jian-Xun Luo; Hong Yin; Zhi-Jie Liu (BMC, 2019)
Abstract Anaplasma species are tick-transmitted obligate intracellular bacteria that infect many wild and domestic animals and humans. The prevalence of Anaplasma spp. in ixodid ticks of Qinghai Province is poorly understood. In this study, a total of 1104 questing adult ticks were investigated for the infection of Anaplasma species. As a result, we demonstrated the total infection rates of 3.1, 11.1, 5.6, and 4.5% for A. phagocytophilum, A. bovis, A. ovis and A. capra, respectively. All of the tick samples were negative for A. marginale. The positive rates of A. phagocytophilum, A. ovis and A. capra in different tick species were significantly different. The positive rates of A. capra and A. bovis in the male ticks were significantly higher than that in the female ticks. Sequence analysis of A. ovis showed 99.5-100% identity to the previous reported isolates. The sequences of A. phagocytophilum had 100% identity to strains Ap-SHX21, JC3-3 and ZAM dog-181 from sheep, Mongolian gazelles, and dogs. Two genotypes of A. capra were found based on 16S rRNA, citrate synthase (gltA) gene and heat shock protein (groEL) gene analysis. In conclusion, A. bovis, A. ovis, A. phagocytophilum, and A. capra were present in the ticks in Qinghai Province. Anaplasma infection is associated with tick species, gender and distribution. These data will be helpful for understanding prevalence status of Anaplasma infections in ticks in Qinghai-Tibet Plateau.